Readability of online patient-based information on bariatric surgery - Zoë Meleo-Erwin; Corey Basch; Joseph Fera; Danna Ethan; Philip Garcia (Tabriz University of Medical Sciences, 2019)
Background: Web-based patient education literature has been shown to be written at reading levels far above what is recommended. Little is known about the overall readability of current internet-based bariatric surgery information. The purpose of this study was to assess the readability of current bariatric material on the internet. Methods: The term "weight loss surgery" was searched using the Chrome browser on the first 15pages of URLs that appeared with content written in English. Using five readability measures, scores were generated using Readable.io for written content on a sample of 96 websites. Scores were sorted into the readability categories of "easy," "average," and "difficult." Results: Almost 93% of websites, both .com and .org, sampled received an unacceptable readability score on each assessment. Conclusion: Accurate and appropriate information about bariatric procedures is critical for patient comprehension and adherence to recommended protocols.